A REVIEW OF ISLAMIC CRIMINAL LAW ON SANCTIONS FOR CHILD RAPE PERPETRATORS ANALYSIS OF LAW NO. 12 OF 2022 ON CRIMES OF SEXUAL VIOLENCE - Kinaryosi, Regi (Program Pascasarjana UIN Sumatera Utara Medan, 2025)
This study discusses the differences in the application of criminal sanctions against perpetrators of consensual sexual relations with children from the perspective of Islamic criminal law and positive law. The focus of the study is on analyzing the verdict in the case of Reza Pratama, who was sentenced to two years in prison under Law Number 12 of 2022 concerning Sexual Violence Crimes (TPKS). In positive law, children are always positioned as victims who cannot be held criminally responsible, even if the act was committed voluntarily. Conversely, Islamic criminal law views sexual relations outside of marriage, whether forced or consensual, as adultery, which is punishable for both parties involved, with the type of punishment determined based on the marital status of the perpetrator. The research method used was normative research with a statute approach and a comparative approach. The results of the study show that there are fundamental differences between the two legal systems. Positive law focuses on the protection of children as a vulnerable group, while Islamic criminal law emphasizes the application of sanctions against all parties who commit adultery without considering age as a determining factor in the status of the victim. This difference reflects the different legal philosophies underlying each system, namely the protection of children's rights in Indonesian positive law and the enforcement of Sharia law in Islamic criminal law